Primary intestinal lymphangiectasia: A rare cause of chronic diarrhea in childhood - Tümay DOĞANCI; F. Nazlı KARA; Mahmut GÖKDEMİR; Arzu ENSARİ; Sıla ÖZALP; Nilgün ÇAKAR; Canan ATAKAN (Turkish Journal of Gastroenterology, 2019)
-